Pemanfaatan Bantuan Pangan Non Tunai (BPNT) Perspektif Maqāṣid Syariah (Studi Kasus di Desa Rappoala Kecamatan Tompobulu Kabupaten Gowa) - Rini Saputri; Dewi Indriani; Fauziah Ramdani (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
The research aims to determine the process of administering and receiving forms of Non-Cash Food Assistance (BPNT) in Rappoala village, Tompobulu sub-district, Gowa district and to understand the analysis of sharia maqāṣid in Non-Cash Food Assistance (BPNT) in Rappoala village, Tompobulu sub-district, Gowa district. The research is qualitative research, by collecting field data related to the problem being studied using a normative and phenomenological approach. The results of the research found that the government policy issued Non-Cash Food Assistance (BPNT) in accordance with maqāṣid sharia in several forms of maintaining maqāṣid sharia, namely protecting religion (hifẓ al-Din), protecting the soul (hifẓ al-Nafs), protecting the mind (hifẓ al-Din). 'Aql), and guarding wealth (hifẓ al-Māl). However, there is one form of maintaining maqāṣid sharia that is not fulfilled, namely, protecting offspring (hifẓ al-Nasl). This policy can normatively save poor groups from the dangers of food insecurity and the danger of losing their lives. However, if you look at some of the existing information and data, Non-Cash Food Assistance (BPNT) in Rappoala village, Tompobulu sub-district, Gowa district is not yet fully in accordance with the maqāṣid sharia al-Hājiyāt (secondary), due to the implementation of Non-Cash Food Assistance (BPNT) in Rappoala village, sub-district Tompobulu, Gowa district, is not in accordance with BPNT regulations, technical guidelines and guidelines, so there are still things that are not on target. so that Non-Cash Food Assistance (BNPT) given to people who are classified as well-off does not cause benefits but instead causes problems. Many poor people feel that they are treated unfairly because they actually have the right to receive assistance but instead they do not receive this assistance.